Rekonstruksi 3 Dimensi dari Video menggunakan Metode Structure-From-Motion (Studi Kasus: Wilayah Pertambangan Batubara) - Rimba Anditya Kurniawan; Fatwa Ramdani; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Indonesia is a country that have a massive natural resources for producing coal. With total 466.307.241 ton in 2012, Indonesia archive third place world level as the most producer coal. For manage coal mining sites, management process very needed. The mine management process can be done with 3-dimensional point clouds reconstruction using the Structure-of-Motion Method (SfM). To build structure from overlapping of many images by using photogrammetry techniques use SfM algorithm. When acquisition image data, sometimes get a failure of automatic camera trigger and lack of density between images. This study uses video data from UAVs flown over mining areas to record all mining activities. Video data predicted can reduce errors during image capture and increase the overlap value between successive images and increase the number of cloud points. The output on the software is tested using the Simple Regression method. This study shows that input video data with 1 minute duration and 90% overlap value can produce 2910 point cloud. The Simple Regression test result an F value of 12,408. It shows that the greater value of overlap, can produce a lot number of points cloud.